Benin - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Benin remains at moderate risk of external debt distress. The rating is unchanged from the previous November 2018 DSA. All the projected external debt burden indicators remain below their thresholds under the baseline, but the ratio of the present value (PV) of external debt to exports exceeds its threshold in the case of an extreme shock to exports.1 With regard to total public and publicly guaranteed (PPG) debt (external plus domestic), the overall risk of debt distress remains also moderate. The public debt-to-GDP ratio is below its prudent benchmark in the baseline scenario; however, the PV of public debt-to-GDP rises very slightly above its benchmark from 2024 until the end of the projection period under the real GDP shock scenario. Other factors motivating the overall rating include: the past evolution of domestic debt, the relatively high debt service burden, as well as the existence of contingent liabilities. Medium-term fiscal consolidation, sound public investment management, and enhanced debt management capacity are needed to reduce debt vulnerabilities.